Empreendedorismo sob o prisma do desenvolvimento sustentável e da responsabilidade socioambiental - Silva, Cristiane Queli da (2012)
Economic activity is one of many sustainable development interfaces. Together with social and environmental pillars sustainability tripod can not exist without the economy one. At the same time economic activity is the major responsible for natural resources depletion, social mindfulness is still incipient regarding the need to preserve natural resources to man worthy survival. This reality demands an out of the box look into entrepreneurship, in order to see it not only as one of the main players of environmental depletion, but also as an opportunity to build bridges to connect us to the ever sought sustainable development and social and environmental responsibility. This work addresses the legal interface of such themes economic activity and environmental preservation and the tools that can be used to trigger collective motivation in natural resources preservation to current and further generations, highlighting, in this work, two of them, environmental education on masters and PHDs courses, extensions, graduation and technical specialization professionally designed to entrepreneurs and managers, because they are the decision makers that can impact natural resources, and public policies, given the State incapacity to efficiently protect the general collective public interests in environmental preservation, in such scenario a company can fill the gap and put social and environmental responsibility actions into practice, as to function as lever to sustainable development, keeping its legitimate primary economic objectives to its shareholders, even more so because sustainability can provide a competitive advantage to be materialized into positive economic results. As a result of the research taken, this work concludes that entrepreneurship can sponsor social and environmental interest and environmental responsibility increase and doing so contribute to the current and further generations worthy lives